Business schools’ students willingness to embrace the principles of global ethics in management education and learning - Nazarina Jamil; Fithriah Ab Rahim; Norhamiza Ishak; Caroline Rosie Jeffrey Nasah (Human Resource Management Academic Research Society (HRMARS), 2024)
Business schools play a crucial role in the development of societies. It is essential for management education to acknowledge and integrate the Principles of Global Ethic into their teaching, in order to promote a socially responsible and sustainable approach to business practices. This study aims to investigate the willingness of business school students to commit the Principles of Global Ethics in their daily lives, and their ability to apply these principles in the workplace. The methodology used to assess students' commitment is discussed, along with an analysis of the findings. The findings provide a basis for understanding the current lack of emphasis on embedding these principles into management education and training, both in business schools and corporate settings. We contend that researchers and educators in the field of management should contribute to a transformative reimagining of humanity's trajectory and implement the necessary changes to management education and learning towards a more just, peace and sustainable world.